The Influence of Audit, Supervision, and Taxpayer Compliance on Revenue Performance, Moderated by Tax Officer Training - Yulianto, Sigit; Ardini, Lilis (Research Horizon, 2025)
Tax revenue performance is a key indicator of fiscal effectiveness and relies on strong administrative functions and taxpayer behavior. This study seeks to examine the impact of tax audits, supervision, and taxpayer compliance on tax revenue performance, while explicitly assessing whether tax officer training moderates these relationships. The study employs a saturated sampling technique and applies a quantitative causality design using multiple regression and moderated regression analysis. The findings indicate that tax audits have a positive but insignificant effect on tax revenue performance, whereas supervision and taxpayer compliance show positive and significant effects. Additionally, tax officer training is found to positively and significantly moderate the effects of audits, supervision, and taxpayer compliance, suggesting that these variables become more influential when supported by higher levels of training. In conclusion, the study highlights supervisory quality and taxpayer compliance as primary drivers of tax revenue performance. The significant moderating role of tax officer training underscores the importance of strengthening human resource capacity to enhance the overall effectiveness of tax administration.